An Empirical Study of Pragmatic Failure by Kurdish EFL Learners in the Performance of Conversational Implicature - I. Mohammed, Mohammed (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
This study investigates the pragmatic failure of Kurdish EFL learners in the performance of conversational implicature. This study is based on a quantitative research method, and an MCQ is used as a tool to collect the necessary data. 35 fourth-year students (24 female, 11 male) from the English Language Department, Cihan University/Sulaimaniya participated in this study. It is found that the main reason of pragmatic failure is because of the learners’ limited language proficiency and that they cannot fully recognize when the relevance maxim is violated. It is also found that they do not quite understand the act of face management. The results demonstrated that Kurdish EFL learners lack the pragmatic knowledge needed to perform conversational implicature. To avoid future pragmatic failure the learners need to be more proficient in the target language with a deeper insight of the socio-cultural norms of the target language.